Self Efficacy as a Mediator between Positive Parenting and Academic Resilience in Adolescents - Khamsiah, Nadya Viranti; Izzaty, Rita Eka (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Academic resilience has emerged as a problem in education and mental health among society, especially among teenagers. Positive parenting and self-efficacy are supporting factors that help adolescents develop academic resilience. This research aims to prove the influence of self-efficacy as a mediator between positive parenting and academic resilience in adolescents. This study employed a quantitative research design, specifically an ex-post facto, with a sample size of 302 adolescents. The sample for this research was determined using an accidental sampling technique. Data collection for this research involved the use of the Academic Resilience Scale-30 (ARS), positive parenting scale, and self-efficacy scale. The validity test employed factor loading results, while the reliability test utilized Cronbach's Alpha. The reliability coefficient values for the academic resilience scale, positive parenting scale, and self-efficacy scale are 0.911, 0.897, and 0.879, respectively. The data analysis utilized various techniques of multiple regression analysis. The findings of this study suggest that favourable parenting characteristics have a moderating effect on academic resilience. The impact of favourable parenting factors on academic resilience, initially at 27.1%, increases to 30.5% when the self-efficacy variable is considered.